The Existence Of Islamic Spiritual Culture In Shaping Students' Spiritual Character - Salikurrahman, Salik; Haningsih, Sri (el-Tarbawi, 2025)
The development of the tourism sector in the Mandalika Special Economic Zone (SEZ) has significantly influenced the socio-cultural dynamics of the local community, including the educational sphere. A major concern is the potential erosion of Islamic spiritual values among the younger generation as a result of rapid cultural globalization. This study aims to explore the existence of Islamic spiritual culture in schools in Kuta Village, Pujut District, Central Lombok, and to identify the challenges, opportunities, and strategies implemented to preserve Islamic values amid the rapid growth of tourism. This research employs a qualitative method with a field study approach, using participatory observation, in-depth interviews with principals, teachers, and community leaders, as well as documentation. Informants were chosen purposively, while the data were analyzed using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. Findings reveal that Islamic spiritual culture remains well preserved in schools through the habituation of religious activities, the integration of Islamic values into learning, and teacher role modeling. Nevertheless, challenges persist, such as the influx of hedonistic culture, weakening parental supervision, and shifts in students’ social orientation. Conversely, tourism also creates strategic opportunities for schools to position themselves as centers for Islamic value education for both students and the surrounding community. This study underscores the vital role of schools in sustaining spiritual values while contributing to the development of Islamic education concepts that are environmentally responsive and relevant to religious-based policy formulation in the Mandalika area.